The Role of Bhayangkara Trustees of Community Security and Order Based on the Head of National Police Regulation No. 3 of 2015 Concerning Community Policing in Preventing Inter-Group Fights in Baubau City - La Gurusi; Muchsin Aziz (Gerechtiheid Law Journal, 2020)
Indonesia has the Republic of Indonesia's National Police Unit as a state instrument that has the role of maintaining security and order. This research aims (1) To find out the role of Bhayangkara Trustees of Community Security and Order (BTCSO) in the prevention of fighting between groups in Batupoaro District. (2) To find out the obstacles faced by BTCSO in preventing inter-group fighting in Batupoaro District. This study uses a qualitative method. The role of BTCSO in preventing inter-group fights in Batupoaro Subdistrict is that BTCSO conducts fostering of community members by making efforts through Pre-emptive, preventive and repressive activities. "Batupoaro namely: a) Internal factors b) External factors.